2018
DOI: 10.1249/mss.0000000000001527
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Modeling of Hamstring Strain Injuries in Elite Australian Footballers

Abstract: Although some iterations of the models achieved near perfect prediction, the large ranges in AUC highlight the fragility of the data. The 2013 models performed slightly better than the 2015 models. The predictive performance of between-year HSI models was poor however. In conclusion, risk factor data cannot be used to identify athletes at an increased risk of HSI with any consistency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
121
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(133 citation statements)
references
References 28 publications
3
121
2
Order By: Relevance
“…Perhaps the limited number of risk factors determined by Ruddy et al [32] to build the models may explain the discrepancy found with the predictive scores reported in the current study. Based on the general agreement that the etiology of HSI is multifactorial and that no powerful individual predictors have been found, the combination of information from several modifiable and non-modifiable risk factors might lead to the development of a more robust model with an improved predictive ability.…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…Perhaps the limited number of risk factors determined by Ruddy et al [32] to build the models may explain the discrepancy found with the predictive scores reported in the current study. Based on the general agreement that the etiology of HSI is multifactorial and that no powerful individual predictors have been found, the combination of information from several modifiable and non-modifiable risk factors might lead to the development of a more robust model with an improved predictive ability.…”
Section: Discussioncontrasting
confidence: 92%
“…The predictive ability of the model developed in the current study to identify athletes at high risk of HSI is higher than the model used in the only study published to date that has used supervised learning algorithms with the aim of predicting the incidence of HSI in Australian footballers [32]. Ruddy et al investigated the ability of some individual (age, history of HSI last season, stature, mass and primary playing position) and strength (eccentric hamstring strength) risk factors to identify Australian footballers at high risk of HSI through the use of some supervised learning algorithms (Naive Bayes, Logistic regression, Random forest, Support vector machine, Neural network) reporting AUC scores lower than 0.6.…”
Section: Discussionmentioning
confidence: 73%
“…Over the last few years, the first studies using predictive analysis in sports injury research were conducted [6,9,16,17]. Previous studies have, however, focused solely on the prediction task with-out paying attention to the explainability of the models.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have, however, focused solely on the prediction task with-out paying attention to the explainability of the models. In addition, two of the studies also used a very low number of variables (from 3-11), although a larger set might have increased the accuracy [9,16]. The need and potential of predictive machine learning methods in sports injury prediction have been recognized, but more research is needed [12,17].…”
Section: Introductionmentioning
confidence: 99%
“…The calculation involves the assessment of the current 1-week workload (acute) relative to the chronic workload (typically 2, 3, or 4-weekly average) [5]. Previous research has used a combination of ACWR and/or accumulated weekly TLs to investigate the relationship with injury across a range of sports, including: rugby [14][15][16][17][18][19], Australian rules football (AFL) [20][21][22][23][24][25][26], American football [27,28], handball [29], Gaelic football [30], and soccer [12,[31][32][33][34][35][36][37]. Despite this growing body of research, there have been conflicting findings within the literature.…”
Section: Introductionmentioning
confidence: 99%